Kit and Worksheet Construction for Isolation Graphene Experiment Based on Guided Inquiry Learning to Improving High School Students View Nature of Science and Technology - Gozali, Haris; Mudzakir, Ahmad; Arifin, Mulyati; Permatasari, R Tiara (IJCAR: Indonesian Journal of Classroom Action Research, 2024)
This research is based on the findings of the 2000-2015 PISA study which shows the low literacy skills of Indonesian students. Learning in schools that focuses too much on content is a major problem. This research seeks to improve by strengthening students' understanding of the nature of science (NOS) and technology (NOT) through technoscience activities, which are expected to increase students' understanding of the nature of science and technology (VNOST). Specifically, this research was carried out to construct a guided inquiry practical kit and worksheet for ionic liquid-based graphene isolation for students. The results of the curriculum suitability analysis and the results of the optimization of ionic liquid-based graphene isolation procedures are in accordance with the stages in the Model of Educational Reconstruction (MER) design research method. Based on the results of a study of graphene technology literature, it was found that the basic ideas of knowledge about graphene technology are in accordance with school chemistry concepts and can be used as an interesting, potential and applicable chemistry learning context or theme and are in accordance with the content of the revised 2013 curriculum. These findings are constructed in such a way as to produce worksheets that are appropriate to students' ability levels, integrated with VNOST, and applicable in accordance with contemporary developments in science and technology. Results indicated significant improvements in VNOST skills, with students demonstrating better understanding and application of scientific concepts.